Revisiting the Optical Band Gap in Epitaxial BiFeO3 Thin Films. Issue 2 (19th December 2017) - Sando, Daniel; Carrétéro, Cécile; Grisolia, Mathieu N.; Barthélémy, Agnès; Nagarajan, Valanoor; Bibes, Manuel
Abstract: A detailed structural and optical band gap characterization study for more than 40 epitaxial bismuth ferrite (BiFeO3 —BFO) thin films, measured by X‐ray diffraction, atomic force microscopy, and optical transmission spectroscopy, is reported. The films are grown in different deposition systems to varying thicknesses (10–140 nm), on several substrates, and under different growth and cooling conditions. Using the results and literature data, first it is shown that the band gap measured by transmission is systematically lower than the gap found by ellipsometry, suggesting that sufficient caution must be exercised when comparing optical properties of BFO thin films. Then, statistical analysis is used to look for correlations between the band gap and structural parameters. While earlier works show the band gap to be sensitive to epitaxial (homogeneous) strain, it is found that it appears not to exhibit a dependence on inhomogeneous strain, out‐of‐plane lattice constant, or substrate/film interface roughness. Rather, it is found that surface roughness as well as film thickness generally tends to enhance the gap. Overall, the insensitivity of the band gap to structural parameters—aside from homogeneous strain—makes BiFeO3 largely immune to deviations in processing parameters, which should be an asset for photonic devices based on this material. Abstract : Using transmission measurements on a large ensemble of epitaxial films, the authors show that the optical band gap of epitaxial BiFeO3 films is largely insensitive to a wide range of processing parameters, including growth temperature, oxygen pressure, and strain gradients in the films.